Rasio lingkar pinggang tinggi badan dan aktivitas fisik sebagai risiko prediabetes remaja kota jambi - Egy Sunanda Putra; Junita Junita (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2022)
Background: Prediabetes is the stage of tolerance between normal glucose and diabetes which is characterized impairment fasting glucose. Prediabetes is an important concern because it increases the risk of diabetes mellitus. Waist-to-height ratio and physical activity is an indicator related to the risk of prediabetes that needs to be studied. Objective: Analyze waist-to-height ratio and physical activity with the risk of prediabetes in adolescents in Jambi City. Methods: a cross-sectional analytic observational study was conducted at SMAN 2 Jambi City in August – September 2019. The subjects were 140 people, the subject was taken by purposive sampling. Waist-to-height ratio data was taken using a metlitmeter and microtoise, physical activity data using the International Physical Activity Questionnaire Short Form (IPAQ-SF). Prediabetes data with fasting blood glucose examination biosystem method using a spectrophotometer biochemical analyzer AE-600N at a wavelength (λ) 500 nm. Data analysis with chi-square and multiple logistic regression. Results: the relationship between waist-to-height ratio (p=0.05; OR=2.615; CI=1.076 – 6.357) and physical activity (p=0.02; OR; 4.380; CI; 1.237 – 5.502) with the risk of prediabetes. physical activity <600 METs-minute/week had 5 times the risk of prediabetes (p=0.02) after being corrected for variables such as waist circumference, height, carbohydrate intake, and total fat. Conclusion: physical activity <600 Mets-minute/week risk factor for prediabetes